THE EFFECT OF FOREIGN DEBT, EXPORTS AND LABOR ON GROSS DOMESTIC PRODUCTS IN INDONESIA 1991-2020 - Olilingo, Fahruddin Zain; Husin, Fatma; Santoso, Ivan Rahmat (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of foreign debt, exports, and labor on Gross Domestic Product. This research is a quantitative study using Indonesian secondary data from 1991 to 2020. The data analysis technique uses time series data analysis with ECM (Error Correction Model). The results showed that: (1) External debt variable had a negative effect (0.050382) and was not significant (0.5611) in the long term and consistently had a negative effect (-0.258494) and not significant (0.11161) in the short term. This shows that any increase in the external debt variable will reduce the value of Indonesia's Gross Domestic Product in the long and short term. (2) The labor variable has a negative effect (-0.006608) and is not significant (0.9800) in the long term and consistently has a negative effect (-0.017525) and not significant (0.9177) in the short term. This shows that every increase in the percentage of the labor variable will reduce the value of Indonesia's Gross Domestic Product in the long and short term. (3) The export variable has a positive effect (1.168843) and is significant (0.0002) in the long term and consistently has a positive effect (0.347710) but not significant (0.2762) in the short term. This shows that every increase in the percentage of the export variable will reduce the value of Indonesia's Gross Domestic Product significantly in the long term but not significantly in the short term.